Phonemic Awareness Deficits in Specific Learning Disorder with Impairment in Reading in Malayalam: A Case-control Study - Anjana Soman; Sonu S. Dev; Rajith Ravindren (Indian Journal of Psychological Medicine, 2026)
Background: Phonemic awareness deficits are a core feature of specific learning disorder with impairment in reading (SLD-R) in alphabetic languages. How task- and language-specific factors influence these deficits in alphasyllabary languages may help clarify the cognitive mechanisms underlying reading impairment in SLD-R. Methods: Thirty children with SLD-R (mean age 11.4 years) and 29 age-matched typically developing children were given phoneme blending (words and pseudowords) and segmentation tasks in Malayalam, an alphasyllabary language. Results: Children with SLD-R performed significantly worse than controls across most phonemic awareness tasks, with the largest deficits observed in pseudoword blending and word blending, and smaller deficits in segmentation. In typically developing children, age showed strong positive correlations with phonemic performance across most tasks. In contrast, the SLD-R group showed weak or absent correlations, except in word blending and initial phoneme deletion. Consonant clusters significantly affected performance in both groups, with SLD-R showing more severe deficits. Conclusions: Phonemic awareness deficits observed in SLD-R in Malayalam are more pronounced in tasks lacking lexical support, such as pseudoword blending. These deficits vary across task types and linguistic complexity. The findings suggest that phonemic awareness deficits are a core feature of SLD-R across languages, but orthographic, and linguistic characteristics of the writing system shape their manifestation.